Kajian Tentang Pengaruh Guest Comment Terhadap Perubahan KebijakanBanquet Manager di Hotel Grand Keisha Yogyakarta - Fera Nurul Permatasari; Budi Purnomo; Denny Asmara (Sekolah Tinggi Pariwisata Sahid Surakarta, 2020)
The purpose of this final project examines the effect of guest comments on changes in banquet policies. In writing this final project, used interviews, questionnaires, observation, literature study and documentation with qualitative descriptive analysis. The results of this study prove the influence of guest comments regarding changes in services, facilities, hotel conditions and security. This is based on the recapitulation of the percentage of information that the respondents answered